An unusual "venous circle" of the internal mammary vein encountered during microvascular anastomosis and implications for practice. Issue 1 (1st January 2020) - Samaras, S.; McKelvie, M. A.; Oni, G.; Malata, C. M.
Abstract: The internal mammary vessels are commonly used for anastomosis in breast reconstruction. The anatomy when using the 2nd ICS has been shown to be predictable and hence preferentially used by the senior author. We present an unusual case of internal mammary vein bifurcation and immediate confluence forming a 'venous circle'.